INTEGRASI KETERAMPILAN MENULIS DALAM PENGAJARAN AIK DI MI MUHAMMADIYAH PONOROGO: SEBUAH PENDEKATAN MULTIDISIPLINER - abdul_aziz; Romadona, Novia; Sumaryanti, Lilis; Katni , Katni (AL IBTIDAIYAH: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2025)
This study aims to examine the influence of the integration of writing skills in the teaching of AIK (Aqidah Akhlak) at MI Muhammadiyah Ponorogo on the understanding of religious materials and the improvement of students' writing skills. The method used is a qualitative approach with a descriptive design, through observation, interviews, and analysis of student written documents. The results of the study show that the integration of writing skills in AIK learning can improve students' understanding of religious materials, as well as help students to connect religious teachings with their personal experiences. Despite the improvement in the quality of writing, there is a variation in writing skills among students, with some showing excellent skills, while others still have difficulty in composing ideas in writing. These findings point to the importance of special attention to individual differences and the need for further support for students who need help with writing skills.